Self-aligned-gate AlGaN/GaN heterostructure field-effect transistor with titanium nitride gate - 张家琦 王磊 李柳暗 王青鹏 江滢 朱慧超 敖金平 (Chinese physics B, 2016)
Self-aligned-gate heterostructure field-effect transistor（HFET） is fabricated using a wet-etching method.Titanium nitride（TiN） is one kind of thermal stable material which can be used as the gate electrode.A Ti/Au cap layer is fixed on the gate and acts as an etching mask.Then the T-shaped gate is automatically formed through over-etching the TiN layer in 30% H2O2 solution at 95 ℃.After treating the ohmic region with an inductively coupled plasma（ICP） method,an Al layer is sputtered as an ohmic electrode.The ohmic contact resistance is approximately 0.3 Ω·mm after annealing at a low-temperature of 575 ℃ in N2 ambient for 1 min.The TiN gate leakage current is only 10^-8 A after the low-temperature ohmic process.The access region length of the self-aligned-gate（SAG） HFET was reduced from 2 μm to 0.3 μm compared with that of the gate-first HFET.The output current density and transconductance of the device which has the same gate length and width are also increased.